The effects of thinning intensity on the growth of oriental beech (Fagus orientalis Lipsky) plantations in Trabzon, NE Turkey : Utjecaj intenziteta prorjeda na rast azijske bukve (Fagus orientalis Lipsky) u plantažama u Trabzonu na sjeveroistoku Turske - Usta, Ayhan (Array, 2019)
In this study, the effects of first thinnings having different intensities in oriental beech (Fagus orientalis Lipsky) plantation areas were investigated in terms of diameter and height growth of trees. Sample plots were chosen from oriental beech plantation areas which are within the boundaries of Maçka–Yeşiltepe and Vakfıkebir districts of Trabzon province, Turkey. With removing of 0%, 10%, 25% and 40% of basal area in a hectare of stands which are in sapling stage, sample plots were established by applying thinnings which are in four different intensities (control, light, moderate, strong). After the thinning applications, basal areas were calculated by measuring diameters and heights of trees in established sample plots in order to reveal stand growth. The effects of thinnings were revealed related to some stand characteristics (average diameter, basal area, average height, relative diameter increment, etc.) and determined chosen trees. The effect of thinning intensity on average diameter, basal area, and volume values is statistically important in every two plantations. 2-year results showed that thinning increased the diameter increment significantly, and the increase in diameter increment was positively correlated with the thinning intensity in both experiments. Moreover, increments of diameter, height, basal area, and volume were higher in Maçka-Yeşiltepe experiment than in Vakfıkebir experiment. But, the values of moderate and strong thinning intensities applied in Vakfıkebir were close to each other. When all the results are evaluated, application of strong thinning intensity for Yeşiltepe sample plot, the moderate thinning intensity for Vakfıkebir sample plot is seen appropriate by us in terms of both stand development.